PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI MEDIATOR - Rafi, Amanullah Rasyid; Nugroho, Dian Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research aims to examine the effect of Service Quality on Customer Loyalty with Customer Satisfaction as the mediating variable. The type of research is descriptive research which is part of empirical research the data is in a numerical form. The research collected 118 respondents through online questionnaires. The research sample consists of respondents as young as 20 years old and respondents who have used ShopeeFood in the last one-year period. SEM-PLS and hypothesis testing were used to analysed the data assisted by SmartPLS and Sobel Test. From the results of four hypotheses testing, it can be concluded that Service Quality has a positive effect on Customer Satisfaction. Service Quality has significant effect on Customer Loyalty. Furthermore, Customer Satisfaction has a positive effect on Customer Loyalty and can mediate the relationship between Service Quality and Customer Loyalty.